Supporting disorders of learning and co-ordination effective provision for dyslexia, dysgraphia, dyscalculia and dyspraxia - Farrell, Michael 1948-; Farrell, Michael 1948- (The effective teacher's guides, 2022)
"This revised and updated third edition, previously titled The Effective Teacher's Guide to Dyslexia and other Learning Difficulties (Learning Disabilities), unravels the complexity of specific learning difficulties in an accessible and user-friendly way. Each chapter provides key information about the disorder in question, giving a clear definition before discussing prevalence, causal factors, identification and assessment and provision. Implications for the curriculum and related assessment, pedagogy, resources, therapy/ care, and school and classroom organisation are explained, allowing providers to reflect and adapt their practice in response to the needs of the individual. The book informs effective provision, with the aim of encouraging the best achievement and personal and social development for children and young people. The book authoritatively and lucidly addresses issues associated with: Impairment in reading/ dyslexia Impairment in written expression/ dysgraphia; Impairment in mathematics/ dyscalculia; Developmental coordination disorder/ dyspraxia Recognising the importance and the challenge of multi-professional working, the book relates provision to the roles of parents and carers alongside that of the practitioner. Underpinned by research and widely held professional judgement, this will prove a practical, readable, and inspiring resource for professionals in the UK, US and elsewhere including teachers, therapists, psychologists, and students entering these professions"--